Automation, big data and politics: a research review - Shorey, S; Howard, P (University of Southern California, Annenberg School for Communication & Journalism, 2016)
We review the great variety of critical scholarship on algorithms, automation, and big data in areas of contemporary life both to document where there has been robust scholarship and to contribute to existing scholarship by identifying gaps in our research agenda. We identify five domains with opportunities for further scholarship: (a) China, (b) international interference in democratic politics, (c) civic engagement in Latin American, (d) public services, and (e) national security and foreign affairs. We argue that the time is right to match dedication to critical theory of algorithmic communication with a dedication to empirical research through audit studies, network ethnography, and investigation of the political economy of algorithmic production.